Controlling the work function of a diamond-like carbon surface by fluorination with XeF2 - Tarditi, Ana Maria (2010)
Thin diamond-like carbon films were subjected to fluorination with gaseous XeF2 under ultrahigh vacuum conditions in order to increase the work function of the diamond-like carbon surface. Changes in the work function and surface composition were monitored with UV photoemission spectroscopy (UPS) and x-ray photoemission spectroscopy (XPS), respectively. Successive XeF2 exposures raised the work function by as much as 1.55 eV. Surprisingly, approximately half of the increase in the work function occurred while the coverage of fluorine remained below 0.02 monolayers (ML). This suggests that initial doses of XeF2 remove extrinsic adsorbates from the diamond-like carbon film and that fluorine desorbs with the reaction products. Increasing the exposure of the diamond-like carbon to XeF2 leads to the expected covalent fluorination of the surface, which saturates at fluorine coverages of 6 F atoms/nm2 (~0.3 ML). Annealing of the diamond-like carbon to temperatures above 850 K was required to reduce the surface fluorine concentration to undetectable levels. This did not, however, cause the work function to return to its original, pre-fluorination value.